TANTANGAN OPTIMALISASI PERAN LABORATORIUM TV DI PERGURUAN TINGGI - Hanny Hafiar; Jimi N Mahameruaji (Profetik: Jurnal Komunikasi, 2017)
The conditions of television in the country are experiencing rapid development. It is characterized by the increasing emergence of private tv stations. The increase in the quantity of television station is a strategic opportunity for the College that has a course-based audiovisual media production. The television laboratory facilities are required to prepare graduates who are ready to use in the television industry. However, to manage the laboratory which ready to serve the internal and external public is not an easy step, there are a number of constraints that became its own challenges for the manager. Therefore, this research attempts to examine more deeply about the challenges faced in the effort to optimize the role of the laboratory in college. The method used is the descriptive method of data collection through interviews and observation and literature study. As for the results obtained include constraints concerning aspects of facilities, human resources, and management of laboratory related to various policy management.